2017
DOI: 10.1016/j.rvsc.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excoecaria agallocha on non-specific immune responses and disease resistance of Oreochromis niloticus against Streptococcus agalactiae

Abstract: The current study was designed to evaluate the effects of Excoecaria agallocha leaf extracts on immune mechanisms and resistance of tilapia, Oreochromis niloticus, after challenge with Streptococcus agalactiae. Fish were divided into 6 groups; groups 1-5 fed with E. agallocha leaf extracts at 10, 20, 30, 40 and 50mgkg level, respectively. Group 6 were fed without extract addition and acted as control. E. agallocha extracts were administered as feed supplement in fish diet for 28days and the hematological, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
6
14
0
Order By: Relevance
“…The augmentation of both serum lysozyme and serum bactericidal activity strengthened the immunostimulant effect of Indian lotus on fish. Similar improvements in serum bactericidal activity were reported in Nile tilapia fed on Excoecaria agallocha (Laith et al, ). Moreover, administration of Ixora coccinea in ornamental goldfish, Carassius auratus (Anusha, Thangaviji, Velmurugan, Michaelbabu, & Citarasu, ) and Henna, Lawsonia inermi s, in common carp (Soltanian & Fereidouni, ) induced increased serum killing activity.…”
Section: Discussionsupporting
confidence: 75%
“…The augmentation of both serum lysozyme and serum bactericidal activity strengthened the immunostimulant effect of Indian lotus on fish. Similar improvements in serum bactericidal activity were reported in Nile tilapia fed on Excoecaria agallocha (Laith et al, ). Moreover, administration of Ixora coccinea in ornamental goldfish, Carassius auratus (Anusha, Thangaviji, Velmurugan, Michaelbabu, & Citarasu, ) and Henna, Lawsonia inermi s, in common carp (Soltanian & Fereidouni, ) induced increased serum killing activity.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, the highest lysozyme activity was observed in the concentration of high dose treatment. Similar to our results, evaluation of lysozyme activity has been reported with thoodhuvalai (Solanum trilobatum) and heart‐leaved moonseed (Tinospora cordifolia) in Mossambique tilapia, Oreochromis mossambicus (Alexander, John Wesly Kirubakaran, & Michael, ; Divyagnaneswari, Christybapita, & Michael, ); holy Basil ( Ocimum sanctum) in rohu, Labeo rohita (Das, Raman, Saha, & Singh, ); peppermint (Mentha piperita) in Caspian brown trout, Salmo trutta caspius (Adel, Safari, Pourgholam, Zorriehzahra, & Esteban, ); henna (Lawsonia inermis) in common carp (Soltanian & Fereidouni, ); Excoecaria agallocha and Chinese mahogany ( Toona sinensis) in Nile tilapia, Oreochromis niloticus (Laith et al, ; Wu, Liu, Chang, & Hsieh, ), and common dandelion (Taraxacum officinale) and common hawthorn (Crataegus monogyna) in golden pompano, Trachinotus ovatus (Tan, Sun, Chen, et al, ; Tan, Sun, Huang, et al, ). Similar results were noted in common carp fed diets enriched with turmeric powder, Curcuma longa (Abdel‐Tawwab & Abbass, ), or Nile tilapia fed diets enriched with green tea, Camellia sinensis (Abdel‐Tawwab et al, ), American ginseng, Panax quinquefolium (Abdel‐Tawwab, ), or cinnamon ( Cinnamomum zeylanicum ) nanoparticles (Abdel‐Tawwab et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The use of environment-friendly prophylactic and therapeutic agents can reduce such risks. Various herbal bioactive extracts have been used as an alternative approach to control diseases in aquaculture (Gültepe et al, 2014;Laith et al, 2017), and as immunostimulants (Ataguba et al, 2014;Kamble et al, 2015). The present work evaluates the efficacy of aqueous extracts of plants on immuno-hemato parameter and disease resistance of Nile tilapia against S. agalactiae and other fish pathogens (Abutbul et al, 2005).…”
Section: Discussionmentioning
confidence: 99%